THE TRIUMPH IN THE END OF THE TEAR (An Analysis of the Affect Sytem in the Tale of Jorinda & Jorindel) - Rakhmat Martopo, Jati; Djatmika, Djatmika; Santosa, Riyadi (Universitas Negeri Semarang, 2020)
Jorinda & Jorindel is one of the horror tales rewritten by Brother Grimms. Jorinda & Jorindel as the protagonists in this story faced a catastrophe caused by supra-natural terror and kidnapping committed by The Evil Witch. In realizing such narration, language plays a significant role to depict the characters’ feelings or emotional state that gives the text mood. Such language is technically perceived as the affect. It is one of the attitude domains under the theory of appraisal. By applying appraisal framework (J. R. Martin & Rose, 2003) as the development of Systemic Functional Linguistics (SFL) theory, this descriptive qualitative study attempts to describe affect prosody in the tale of Jorinda and Jorindel. The study found that in the orientation the story is full with the good vibe linguistically represented by positive effect felt by the protagonist. It then changes radically into negative affect (antipathy, unhappiness, and insecurity) as well as the antagonist (antipathy), It then begins to return to equilibrium represented by the positive affect in the evaluation (happiness and security). It continues in the resolution where the positive affect (happiness) fulfills the protagonists’ hearts but not with the antagonists’. It is because her evil life has been over. The findings imply that the affect resonates from the positive to negative and returns to positive